2003
DOI: 10.1023/b:ccfp.0000006292.61072.d2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Child and Adolescent Exposure to Community Violence

Abstract: Emerging as one of the most significant health issues facing American youth today, child and adolescent exposure to community violence has generated much interest across multiple disciplines. Most research to date has focused on documenting the prevalence of community violence and the emotional and behavioral ramifications. This paper provides an overview of the current literature regarding prevalence of youth exposure to community violence, and identifies those areas where further research is warranted. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
219
4
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(244 citation statements)
references
References 52 publications
14
219
4
7
Order By: Relevance
“…By making this distinction in our study, we were able to identify a pattern of increasing prevalence of these risk factors from the no trauma to the trauma without PTSD to the PTSD group, which was present for all of the factors examined. In addition, higher rates of both PTSD and trauma in the absence of PTSD were found in African-American women compared with White women, a fi nding that has been reported in a number of prior studies (Breslau et al, , 2004Rheingold et al, 2004;Stein et al, 2003).…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 59%
“…By making this distinction in our study, we were able to identify a pattern of increasing prevalence of these risk factors from the no trauma to the trauma without PTSD to the PTSD group, which was present for all of the factors examined. In addition, higher rates of both PTSD and trauma in the absence of PTSD were found in African-American women compared with White women, a fi nding that has been reported in a number of prior studies (Breslau et al, , 2004Rheingold et al, 2004;Stein et al, 2003).…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 59%
“…In addition, some children are particularly vulnerable to violence exposure. For instance, community violence exposure is particularly prevalent among urban, minority youths of lower socioeconomic status (Stein et al, 2003).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Although numerous studies have documented an association between violence experiences and alcohol use among adults, limited research has investigated the association between interpersonal violence experiences and alcohol use among adolescents. In the general population of adolescents, studies have examined interpersonal violence experiences or childhood maltreatment and various mental health outcomes (for example, Boney-McCoy & Finkelhor, 1995, 1996Margolin et al, 2009;Stein et al, 2003;Voisin, 2007). However, limited research exists on the link between interpersonal violence experiences and alcohol use outcomes in this population (Giaconia et al, 2000;Hamburger et al, 2008;Kilpatrick et al, 2000Kilpatrick et al, , 2003.…”
Section: Interpersonal Violence and Alcohol Usementioning
confidence: 99%
“…Research has found that adolescents are at higher risk than other youth age groups for community violence experiences, with a high prevalence of such experiences (Aisenberg & Herrenkohl, 2008;Stein, Jaycox, Kataoka, Rhodes, & Vestal, 2003;Voisin, 2007). Data on interpersonal violence reveal that more than one-third of 10-to 16-year-olds have been victims of assault (Boney-McCoy & Finkelhor, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation